2021
DOI: 10.3389/fped.2021.679342
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Congenital Myasthenia Caused by Three Mutations in the COLQ Gene

Abstract: The gene encoding collagen like tail subunit of asymmetric acetylcholinesterase (COLQ) is responsible for the transcription of three strands of collagen of acetylcholinesterase, which is attached to the endplate of neuromuscular junctions. Mutations in the COLQ gene are inherited in an autosomal-recessive manner and can lead to type V congenital myasthenia syndrome (CMS), which manifests as decreased muscle strength at birth or shortly after birth, respiratory failure, restricted eye movements, drooping of eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Studies have shown that mutations in COLQ can lead to congenital myasthenic syndrome (CMS), which causes cardiac autonomic dysfunction ( 32 , 33 ). Interestingly, Çubukçuoğlu et al ( 34 ) found that the expression of COLQ was higher in degenerative mitral regurgitation patients with AF than in those with SR ( P = 0.003), which is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that mutations in COLQ can lead to congenital myasthenic syndrome (CMS), which causes cardiac autonomic dysfunction ( 32 , 33 ). Interestingly, Çubukçuoğlu et al ( 34 ) found that the expression of COLQ was higher in degenerative mitral regurgitation patients with AF than in those with SR ( P = 0.003), which is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…COLQ -CMS has been reported in 30 original articles since 1998 [ 62 , 73 , 78 , 140 , 141 , 221 , 222 , 225 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 ]. Interestingly, a grandmother and a father of two siblings with COLQ -CMS carried a heterozygous truncation variant of COLQ , and showed congenital ptosis [ 246 ].…”
Section: Thirty-five Genes In 14 Groups Of Cmsmentioning
confidence: 99%
“…gene= COLQ). Interestingly, truncating mutations that lead to the production of a transcript with premature termination codon result in premature termination of peptide chain synthesis and the formation of a defective protein, which is subsequently degraded by nonsense-mediated mRNA decay (NMD) in order to prevent the expression of truncated proteins with potentially toxic effects [29].…”
Section: Fig 4 Venn Diagram Showing Possible Genes With Their Differe...mentioning
confidence: 99%
“…In 2020, Laforgia et al identified a homozygous extended deletion encompassing exons 11-17, arr [GrCh37] 3p25.1(15491478x1,15492150_ 15511615x0,15511740x1) of the COLQ gene in a Pakistani male child with severe clinical presentation of CMS [11]. Lastly, in 2021, Luo and their colleagues reported deletion of exons 14-15 at homozygous state in a 12-year-old boy with mild symptoms [29] (Table 1).…”
Section: Fig 4 Venn Diagram Showing Possible Genes With Their Differe...mentioning
confidence: 99%